Studi Eksperimental Performansi Sistem Pendinginan Maisotsenko Udara Parallel Flow Dengan Variasi Laju Aliran Massa Udara Primer - Ramadhan, Tegar; Wijaksana, Hendra; Surya, I Gede Teddy Prananda (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstract Energy demand continues to rise along with urbanization, energy availability, and population growth. About 50% of energy is used for building cooling. Conventional cooling systems, such as vapor compression, are energy-intensive and contribute to global warming. A more efficient and environmentally friendly solution is evaporative cooling techniques, but the effectiveness of evaporative coolers is generally low, which is their main drawback. However, there is a new thermodynamic cycle known as the Maisotsenko cycle, whose purpose is to cool the incoming air into the wet channel through the dry part of the wet channel. In this study, a Maisotsenko cooler with parallel airflow was used with variations in primary air ????? of 0.0553 kg/s, 0.0415 kg/s, and 0.0276 kg/s, while the secondary ????? was kept constant at 0.0691 kg/s. Data collection was conducted on the primary air temperature, secondary air temperature, and working air temperature. At a primary air ????? of 0.0276 kg/s, the temperature drop, wet bulb effectiveness, and dew point effectiveness reached their highest values of 2.1°C, 27.63%, and 19.81%, respectively. When the primary air ????? was 0.0415 kg/s, the cooling capacity increased to the highest value of 58.45 W. Additionally, at a primary air ????? of 0.0276 kg/s, the Energy Efficiency Ratio (EER) reached 48.6%. Keywords: M-Cycle, Evaporative Cooling, Parallel Flow, Cooling System, Temperature Drop